2014
DOI: 10.1161/jaha.114.000899
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Knockdown of Cardiac Sodium/Glucose Cotransporter 1 (SGLT1) Attenuates PRKAG2 Cardiomyopathy, Whereas Transgenic Overexpression of Cardiac SGLT1 Causes Pathologic Hypertrophy and Dysfunction in Mice

Abstract: BackgroundThe expression of a novel cardiac glucose transporter, SGLT1, is increased in glycogen storage cardiomyopathy secondary to mutations in PRKAG2. We sought to determine the role of SGLT1 in the pathogenesis of PRKAG2 cardiomyopathy and its role in cardiac structure and function.Methods and ResultsTransgenic mice with cardiomyocyte‐specific overexpression of human T400N mutant PRKAG2 cDNA (TGT400N) and transgenic mice with cardiomyocyte‐specific RNA interference knockdown of SGLT1 (TGSGLT1‐DOWN) were cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 24 publications
6
67
0
Order By: Relevance
“…SGLT1 expression levels were increased in diabetic or ischemic cardiomyopathy (Banerjee et al, 2009). Although the functional roles of SGLT1 have not been determined in such nonepithelial tissues, it has been reported that SGLT1 is involved in the pathophysiology of a murine model of PRKAG2 cardiomyopathy (Ramratnam et al, 2014). Because the maximal plasma level of unbound canagliflozin in clinical studies (20-60 nM, see above) is ∼1/30 to 1/10 of the K i value for SGLT1 (770.5 nM), the oral administration of clinical doses of canagliflozin would not inhibit SGLT1 in the heart or skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…SGLT1 expression levels were increased in diabetic or ischemic cardiomyopathy (Banerjee et al, 2009). Although the functional roles of SGLT1 have not been determined in such nonepithelial tissues, it has been reported that SGLT1 is involved in the pathophysiology of a murine model of PRKAG2 cardiomyopathy (Ramratnam et al, 2014). Because the maximal plasma level of unbound canagliflozin in clinical studies (20-60 nM, see above) is ∼1/30 to 1/10 of the K i value for SGLT1 (770.5 nM), the oral administration of clinical doses of canagliflozin would not inhibit SGLT1 in the heart or skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…RNA extraction, reverse transcription PCR extraction, cDNA sequencing, and real-time quantitative PCR (QPCR) were performed as we have previously described [1820]. Briefly, total RNA was isolated from whole heart with TRIzol (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, STZ-diabetic T1DM rats have increased cardiac expression of autophagy proteins that are specific for glycogen [139]. Interestingly in this regard, cardiac-specific knockdown of SGLT1 has been reported to prevent glycogen storage cardiomyopathy in a mouse model carrying a mutation in the gene for the gamma2 subunit of AMPK [141, 142]. The relevance of this finding for the diabetic heart has not been tested.…”
Section: Sglt1 In the Diabetic Heart – A Role For Ros Formation Amentioning
confidence: 99%